Association between a functional interleukin 6 receptor genetic variant and risk of depression and psychosis in a population-based birth cohort - Khandaker, Golam M. (Brain Behav Immun, 2018)
OBJECTIVE: Interleukin 6 (IL-6) levels are commonly elevated in patients with depression and psychosis and in people who are at risk of developing these disorders. A common, functional variant in the IL6R gene (IL6R Asp358Ala; rs2228145 A > C) is known to dampen down inflammation by impairing IL6R signaling. We have examined the association of Asp358Ala with diagnosis of depression and psychosis, serum IL-6, CRP levels, and a number of risk factors commonly linked with inflammation, depression or psychosis. We predicted that if IL-6 were related to depression/psychosis risk causally, rather than due to confounding, Asp358Ala would be associated with risk of these disorders, serum IL-6, CRP levels, but not with any of the confounders. METHOD: We used data from the population-based ALSPAC birth cohort. Serum IL-6 and CRP levels were measured at age 9 years. Psychotic disorder, ICD-10 diagnosis of severe depressive episode, and total depression score were assessed at age 18 years. IL6R Asp358Ala was genotyped using the Illumina HumanHap550 quad genome-wide SNP genotyping platform. Risk factors assessed include sex, body mass index, social class, ethnicity, maternal education, birth weight, gestational age, maternal post-natal depression, childhood psychological and behavioral problems, and total IQ score. RESULTS: Asp358Ala was associated with decreased risk of severe depression and/or psychosis; adjusted odds ratio for those with CC, compared with AA, genotype was 0.38 (95% CI, 0.15–0.94). The variant was associated with increased serum IL-6 levels (P = 5.5 × 10(−22)) but decreased serum CRP levels (P = 3.5 × 10(−5)), consistent with an anti-inflammatory effect downstream of IL-6. Asp358Ala was not associated with total depression score. Asp358Ala was not associated with any of the other risk factors commonly linked with inflammation, depression or psychosis (all P > 0.20). CONCLUSIONS: The findings provide further evidence that the IL-6/IL6R pathways are involved in pathogenesis of severe depression and psychosis, and may be novel therapeutic targets. Previously reported associations between IL-6, depression and psychosis are unlikely to be fully explained by confounding. Based on a small number of cases, findings from the current study need replication in other samples.